A Challenging Case Of Amiodarone-Induced Pulmonary Toxicity Presenting As Cryptogenic Organizing Pneumonia Combine With Blue Man Syndrome: A Multidisciplinary Case Report (The Review of Diabetic Studies, 2025)
Background: Amiodarone is a prevalent antiarrhythmic medication with efficacy and a risk for serious adverse effects, most importantly pulmonary toxicity and dermatologic presentation. Amiodarone pulmonary toxicity (APT) can manifest as interstitial lung disease or cryptogenic organizing pneumonia (COP) mimicking infection or malignancy. Blue Man Syndrome is a rare cutaneous appearance that indicates chronic amiodarone exposure in less than 3% of patient using amiodarone medication .Case Presentation: A 57-year-old male patient with a history of mitral valve replacement , 8 years amiodarone therapy who was admitted through the emergency department with dyspnea, dry cough, low-grade fever, and skin discoloration for 10 days. He was initially evaluated for community-acquired pneumonia. But, lack of response to antibiotics and presence of a reversed halo sign on high-resolution CT scan also negative sputum, excluding infectious culture etiology, rendered APT as a cause of COP diagnosis. In addition, Blue Man Syndrome was present in the patient, which was an amiodarone dermatologic side effect. Amiodarone withdrawal and multidisciplinary assessment led to radiologic and clinical improvement.Conclusion: This case stresses the importance of recognizing the pleiotropic toxicities of amiodarone, including pulmonary and cutaneous. Early diagnosis by imaging and clinical correlation and withdrawal of the offending drug in a timely manner are necessary to prevent additional morbidity. Multidisciplinary approach is essential in handling complex adverse drug reactions.